An Interdependence Approach to Empathic Concern for Disability and Accessibility: Effects of Gender, Culture, and Priming Self-Construal in Japan and New Zealand. (14th February 2018) - Miyahara, Motohide; Sawae, Yukinori; Wilson, Rebekah; Briggs, Hahna; Ishida, Jiro; Doihata, Koichiro; Sugiyama, Ayano
Abstract : An interdependence approach to empathic concern could transform the current societal environment for people with disability into a more accessible and equitable one. To our knowledge, this is the first study to investigate two possible factors influencing empathic concern, gender and ethnic culture, in specific helping scenarios. We first examined whether the female gender and collectivist culture of Japan were associated with higher levels of interdependence and empathic concern for disability than were the male gender and individualist culture of New Zealand. Empathic concern for people with impairment was assessed in accessible and inaccessible environments. Neither gender nor culture significantly influenced the level of interdependence, whereas gender and culture differentially moderated empathic concern. We also explored the possibility of altering self-construal and thus promoting prosocial behaviour by examining the correlation between self-construal and prosocial intention, and the effect of cultural priming on self-construal. The correlation was significant under inaccessible conditions in the Japanese sample, and the effect of interdependent priming was not significant on interdependent self-construal in both countries. Discussion centres on theoretical implications of the observed conditional support for the female-gender and collectivist-culture hypotheses, and on ways to promote prosocial behaviour, taking into account gender and cultural differences.